How to Build a Collaborative Model for Express Packaging Recycling –An Evolutionary Game Perspective - Pei, Jianwen; Li, Hui (Journal of Global Economy, Business and Finance, 2025)
As the e-commerce and express delivery industries grow rapidly, the environmental pollution caused by express delivery packaging waste is becoming more serious. The current recycling model is difficult to promote effectively due to its high cost, limited coverage, and low public participation, and there is an urgent need to build a multi-party collaborative governance mechanism based on evolutionary game theory. The study finds that: (1) the government policy intensity has a significant driving effect on the recycling behavior of online shopping platforms, and a reasonable reward and punishment mechanism can accelerate the evolution of its positive strategy; (2) the leading role of the government is especially critical when the initial willingness of consumers to participate is low, and it is necessary to enhance the public’s awareness of environmental protection by means of policy guidance and publicity and education; (3) there is a significant synergistic effect among the three parties, and the government needs to balance the distribution of subsidies between the platforms and the consumers and ensure that the policy benefits are higher than the non-compulsory strategy.